Assessment of Biochemical measurements with vitamin D deficiency in nephrotic syndrome patient - Mangi, Imran; Lashari, Sajid; Kumar, Ranjeet (Pakistan Journal of Kidney Diseases, 2024)
OBJECTIVE: To determine the frequency of vitamin D deficiency and bone mineral metabolism abnormalities in patients with nephrotic syndrome. PATIENTS AND METHODS: Between June to December 2019, all patients who fulfilled the inclusion criteria and visited to SIUT, Karachi were included in the study, which is a descriptive cross sectional study. Informed consent was taken after explaining the procedure, risks and benefits of the study. Blood samples of all the patients were taken for measurement of vitamin D and bone mineral metabolism abnormalities. RESULTS: Out of 92 patients, 51(55.4%) were male while 41 (44.6%) were female Mean ± SD of age was 32.76±10.16 years. Vitamin D deficiency was found in 49 (53.3%) patients. Hypocalcemia occurred in 48 (52.2%) patients. Raised Alkaline phosphate was found in 42 (45.7%) patients. CONCLUSION: It is to be concluded that vitamin D deficiency and bone mineral metabolism abnormalities were documented in considerable number of patients presenting with nephrotic syndrome.